O15.1 Sensitive detection of chlamydia trachomatis pgp3 antibody demonstrates antibody persistence and correlates with self-reported infection and behavioural risks in a blinded cohort study. (13th September 2015) - Horner, P; Wills, GS; Righarts, AA; Vieira, S; Samuel, D; Winston, A; Muir, D; Dickson, NP; McClure, MO
Abstract : Introduction: With improvements in serological detection of Chlamydia trachomatis (CT) infection and knowledge of persistence of CT antibodies, serological studies in populations could help monitor changes in incidence. The Dunedin Multidisciplinary Health and Development study, New Zealand, has regularly monitored the health and behaviour of 1037 men and women since their birth in 1972–73 . Using this cohort, we report on the association between CT seropositivity and age, sexual behaviour and self-reported infection, as well as CT antibody changes over time. Methods: We developed a Pgp3 double-antigen sandwich ELISA then assayed, blinded, sera obtained from the Dunedin cohort at ages 26, 32 and 38. Results: Seropositivity was associated with a history of CT at all ages, with a stronger association in women than men. At ages 26, 32 and 38 years, 24.1%, 26.2% and 26.8% respectively of women, and 10.7%, 14.0% and 13.1% of men, were CT seropositive. Among those with a self-reported prior CT diagnosis at these ages, 79.5%, 75.0% and 74.6% respectively of women were positive, markedly higher than among comparable men (25.0%, 33.3% and 27.0%). The proportion seropositive increased with the lifetime number of sexual partners at all ages (p < 0.001). At age 38, among Pgp3 seropositive individuals 63.3% (95% CI 54.4%–71.4%) of women and 83.1% (71.5%–90.5%) of men did not report having ever been diagnosed with chlamydia. Among women, persistence over six years was 92.5% (85.7–96.7%) and over 12 years 94.3% (87.2–98.1%); among men the respective proportions were 87.3% (76.5–94.4%) and 83.8% (68.0–93.8%). Conclusion: CT infection was common in Dunedin, New Zealand with many infections going undetected. The strong correlation of Pgp3 antibody with number of sexual partners and high persistence of antibody is a powerful argument for the development of methodology to use CT Pgp3 serology for evaluation of CT control programmes. Disclosure of interest statement: PH has received funding from Cepheid directly and indirectly for lecturing on point of care testing and undertaking research on the cost effectiveness of their CT/NG assay. Has also received payment from Atlas Genetics for an article in the Parliamentary Review on the benefits of point of care technology in improving the cost effectiveness of sexual health services. Has also received an honorarium from Hologic for an education talk on STI diagnostics. GW, AR, SV, DS, AW, DM, ND and MMcC no conflicts of interest declared.